"Hooked up to that damn machine": Working with metaphors in clinical ethics cases. (June 2019) - Michl, Susanne; Wohlmann, Anita
The frequent use of metaphors in health care communication in general and clinical ethics cases in particular calls for a more mindful and competent use of figurative speech. Metaphors are powerful tools that enable different ways of thinking about complex issues in health care. However, depending on how and in which context they are used, they can also be harmful and undermine medical decision-making. Given this contingent nature of metaphors, this article discusses two approaches that suggest how medical health care professionals may systematically and imaginatively work with metaphors. The first approach is informed by a model developed by cognitive scientists George Lakoff and Mark Turner. The second approach is a close reading and thus a text-immanent, hermeneutical strategy. Using the double perspective of an ethics consultant and a researcher in literature studies, we take a case from Richard M Zaner in which a metaphor is central to the clinical-ethical problem. The article shows that the approaches, which focus on creativity and the intersections of form and content, may be helpful tools in clinical ethics, enabling a competent and mindful working with metaphors in complex cases as well as supporting the consultant's thoughts processes.